IDENTIFICACIÓN Y ANÁLISIS DE LOS RIESGOS LOCATIVOS EXISTENTES EN LA ALCALDÍA MUNICIPAL DEL LITORAL DEL SAN JUAN, CHOCÓ, DURANTE EL AÑO 2016. (2017)
This research work is based on a problem situation observed in the municipality of San Juan, an area dedicated to administrative management, where there is little interest related to occupational safety and health. The dangers to which the workers of the mayoralty of the coast are exposed, part of the risk factors of locative origin. For this reason, it has been considered advisable to carry out a diagnosis to generate actions and / or measures to prevent, identify, evaluate and control the hazards and risks of this type to which the workers of this entity are exposed in compliance with the legal provisions in force on security and health at work. It was developed taking into account the organizational structure, its facilities, the responsibilities of the workers, the practices, procedures, processes and human and economic resources that the entity has. Thus, the purpose of the investigation was based on the development of its objectives such as: Identification locative to what the officials of the municipality of the coast of San Juan are exposed, analysis of the hazards in the GTC 45 hazards matrix and finally make recommendations According to the findings of hazards found.